PENGUASAAN MANAJEMEN SUMBER DAYA INSANI SEBAGAI PENGELOLAAN MODAL KERJA AKUNTANSI ISLAM - Rahmad Annam (Institut Agama Islam Negeri Padngsidimpuan, 2015)
Abstract This study aimed determine whether there is competency human resource managementcontrolas the working capital accounting islamic theUniversity Students programe study ekonomy syariah semester 1 Level 2014/2015 at the Institut Agama Islam Negeri (IAIN) Padangsidimpuan. The population of University studentsprograme study ekonomy syariah semester 1 Level 2014/2015 at the Institut Agama Islam Negeri (IAIN) Padangsidimpuan. Furthermore to capture the necessary data done with test, in order to obtain data on both variables. Then the research data is processed in two stages: a descriptive analysis t ride an erie and inerential statistial rmula r by earsn rdut ment. ntent ariables in the ategry enugh. hile ariables in the ategry enugh. Based on calculations derived rtest of 0,282. When compared the value obtained rtabel 0f 0,220. It is known that rhitung greater than rtabel (0,2820,220). This means that there is a significant effect between competency of the human resource managementcontrolas working capital theUniversity students programe study ekonomy syariah semester 1 Level 2014/2015 at the Institut Agama Islam Negeri (IAIN) Padangsidimpuan. Keywords: The human resource managementcontrol, working capital Accounting Islam